Organizational culture, strategic planning and performance: empirical evidence from organizations in Malaysia - Samad, Sarminah (International Journal of Engineering and Technology, 2018)
This study examined the influence of strategic planning on organizational performance of selected government organizations in Malaysia. Consequently, it determined the moderating effect of organizational culture on the relationship between strategic planning and organizational performance. A quantitative study was carried out on a sample of 291 officers in Malaysian government organizations. The obtained data based on self-administered questionnaires was analyzed using SmartPartial Least Squares (PLS). The study revealed that strategic planning dimensions have positive effects on performance of government organizations. The results found that organizational culture has significantly moderated the relationship between strategic planning and performance. The implications from the research findings, limitation of study and future research directions are discussed.Â